Judd-Ofelt parameters and X-ray irradiation results of MNb2O6:Eu3+ (M = Sr, Cd, Ni) phosphors synthesized via a molten salt method - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2021)
Trivalent Eu-activated MNb2O6 (M = Sr, Cd, Ni) ceramic phosphors were produced using the molten salt route, which involves a low sintering temperature and provides improved homogeneity. The photoluminescence (PL) and radioluminescence (RL) spectra of phosphors exhibited characteristic Eu3+ emissions with F-5(0) -> F-7(j) transitions, and strong peaks occurred at the D-5(0) -> F-7(2) transition. The PL and RL emissions of SrNb2O6:Eu3+ decreased over 3 mol%, while both emissions for CdNb2O6:Eu3+ and NiNb2O6:Eu3+ increased with increasing Eu3+ concentration. The spectral properties of phosphors were evaluated by determining Judd-Ofelt intensity parameters (omega(2), omega(4)) from the PL emission spectrum. The quantum efficiencies (eta(QE)%) of MNb2O6:Eu3+ (M = Sr, Cd, Ni) phosphors with the highest emission were found as 61.87%, 41.89%, and 11.87% respectively. Bandwidths (sigma(e) x Delta lambda(eff)) and optical gains (sigma(e) x tau) of MNb2O6:Eu3+ (M = Sr, Cd, Ni) phosphors with highest emissions were found as follows; 24.182 x 10(-28), 28.674 x 10(-28), 38.647 x 10(-28) cm(3) and 20.441 x 10(-25), 13.790 x 10(-25), 3.987 x 10(-25) cm(2) s, respectively, corresponding to the D-5(0) -> F-7(2) transition.
Keywords: PHOTOLUMINESCENCE PROPERTIES; EU3+; NANOPHOSPHORS; LUMINESCENCE; INTENSITIES